Clinical Pearls - how my patients taught me: The fainting lark symptom. Issue 1 (December 2016) - Kuiper, A.; van Egmond, M.E.; Harms, M.P.M.; Oosterhoff, M.D.; van Harten, B.; Sival, D.A.; de Koning, T.J.; Tijssen, M.A.J.
Abstract Background Compulsive movements, complex tics and stereotypies are frequent, especially among patients with autism or psychomotor retardation. These movements can be difficult to characterize and can mimic other conditions like epileptic seizures or paroxysmal dystonia, particularly when abnormal breathing and cerebral hypoxia are induced. Case presentation We describe an 18-year-old patient with Asperger syndrome who presented with attacks of tonic posturing of the trunk and neck. The attacks consisted of self-induced stereotypic stretching of the neck combined with a compulsive Valsalva-like maneuver. This induced cerebral hypoperfusion and subsequently dysautonomia and some involuntary movements of the arms. Conclusion This patient suffered from a complex tic with compulsive respiratory stereotypies. His symptoms contain aspects of a phenomenon described in early literature as 'the fainting lark'.